K-State Turfgrass Research 2008 - Kansas State University. Agricultural Experiment Station; Cooperative Extension Service (Kansas Agricultural Experiment Station Research Reports, 2008)
Turfgrass Research 2008 contains results of projects conducted by K-State faculty and graduate students. Some of these results will be presented at the Kansas Turfgrass Field Day, August 7, 2008, at the Rocky Ford Turfgrass Research Center. Articles included in this Report of Progress present summaries of research projects that were completed recently or will be completed in the next year or two. Specifically, this year's report presents summaries of research on environmental stresses and the environment, disease control, and cultivar evaluations.
Keywords: Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 998; Kansas Agricultural Experiment Station contribution; no. 08-352-S; Turfgrass; Stress management; Disease control; Bluegrass; Creeping Bentgrass; Zoysiagrass